Expression level and proteolytic activity of MMP-2 and MMP-9 in dental follicles, dentigerous cysts, odontogenic keratocysts and unicystic ameloblastomas - Josué Zuriel Ortiz-García; Susana Munguía-Robledo; Juan José Estrada-Orozco; Carlos Licéaga-Escalera; Mario A. Rodríguez (Elsevier, 2022)
Matrix metalloproteinases (MMPs) are involved in remodeling the extracellular matrix, but also participate in the development of physiopathologic processes. As they are overexpressed in different types of epithelial cancers, it has been suggested that their level expression could explain the different biological behavior between odontogenic cysts and tumors. Here, we compared the expression level and proteolytic activities of MMP-2 and MMP-9 in dental follicles, dentigerous cysts, odontogenic keratocysts and unicystic ameloblastomas. We found similar expression of MMP-2 in all tissues, but a higher activity in cystic and tumor lesions than follicles. On the other hand, MMP-9 expression and activity was greater in cysts and ameloblastoma than in follicles. However, no differences were found in expression or activity of both MMPs between cystic and tumor injuries, suggesting that they could participate in the growth of these lesions, but they cannot define their different biological behavior.